A study on the lipid ratios and inflammatory markers in pre-diabetic and diabetic patients - Shrestha, Shailaza; Sharma, Preeti; Kumar, Pradeep; Prasad, Mahendra (International Journal of Research in Medical Sciences, 2019)
Background: One of the leading causes of diabetic mortality is cardiovascular disease. Diabetes progression is preceded by pre-diabetic phase which is also at higher cardiovascular risk. Both hyperglycemia and atherosclerotic processes are inflammatory phenomenon. Keeping this in view, it was aimed to evaluate atherogenic indices and correlate them with inflammatory mediators. Methods: This study included 80 controls, 80 pre-diabetic and 80 diabetic patients. Anthropometric parameters (BMI, WHR) and blood parameters like fasting glucose, HbA1c, lipid profile (cholesterol, HDL, LDL TG, VLDL), adiponectin, IL-6, CRP, fibrinogen and uric acid were analysed. Results: Significantly high atherogenic indices were observed in pre-diabetic and diabetic subjects compared to healthy controls. The indices were also significantly correlated with BMI, fasting sugar, HbA1c, cholesterol, HDL, TG and LDL. The correlation with HDL was negative and with other parameters, the correlation was positive. In pre-diabetic patients, adiponectin showed significant negative correlation while fibrinogen and CRP showed significant positive correlation with cardiac risk indices. IL-6 was positively correlated only with AIP while correlation of uric acid with these indices was insignificant. In case of diabetic patients, the cardiac risk indices were significantly correlated with adiponectin, IL-6, CRP, fibrinogen and uric acid. The correlation with adiponectin was negative. Conclusions: The altered atherogenic indices and their significant association with inflammatory markers signify the direct association of inflammation with CVD risks. Thus, there is requirement of novel approaches that can retard inflammatory responses and arrest unwanted cardiac health outcomes.